Astragaloside IV Alleviates Infarction Induced Cardiomyocyte Injury by Improving Mitochondrial Morphology and Function - Zhang, Wen; Zhang, Ling; Zhou, Huifen; Li, Chang; Shao, Chongyu; He, Yu; Yang, Jiehong; Wan, Haitong (Frontiers in Cardiovascular Medicine, 2022)
The protective effect of astragaloside IV (AS-IV) on myocardial injury after myocardial infarction has been reported. However, the underlying mechanism is still largely unknown. We established a myocardial infarction model in C57BL/6 mice and treated them with AS-IV for 28 days. The cardiac function, myocardial fibrosis, and angiogenesis were investigated by echocardiography, Masson’s trichrome staining, and CD31 and smooth muscle actin staining, respectively. Cardiac mitochondrial morphology was visualized by transmission electron microscopy. Cardiac function, infarct size, vascular distribution, and mitochondrial morphology were significantly better in AS-IV-treated mice than in the myocardial infarction model mice. In vitro, a hypoxia-induced H9c2 cell model was established to observe cellular apoptosis and mitochondrial function. H9c2 cells transfected with silent information regulator 3 (Sirt3) targeting siRNA were assayed for Sirt3 expression and activity. Sirt3 silencing eliminated the beneficial effects of AS-IV and abrogated the inhibitory effect of AS-IV on mitochondrial division. These results suggest that AS-IV protects cardiomyocytes from hypoxic injury by maintaining mitochondrial homeostasis in a Sirt3-dependent manner.